Distribution of Nitrogen Ions Generated in the Electrochemical Oxidation of Nitrogen Containing Organic Compounds (2009)
The electro-oxidation, over platinized titanium and ruthenium oxide anodes, of nitrogen containing molecules (urea, reactive Blue 4 dye, acetonitrile, formamide, guanidine and pyridazine) was investigated, monitoring the products distribution. The Numineralization leads to have inorganic pollutants (NH3/NH4+and/or NO2-/NO3-). Amidic and aminic compounds react both in homogeneous (acid hydrolysis) and in heterogeneous phase (direct electroxidation) with a rate depending on the original state of oxidation of nitrogen. Heterocyclic and multiple-bond carbon-nitrogen molecules were effectively converted with negligible mineralization of nitrogen due to the stability of their first oxidation intermediates. The obtained results (high rate of nitrate generation) evidence the need of coupling of the direct electroxidation with other process to limit the nitrate concentration to an accepted level; in accordance, dialysis (of the ammonia cation) and indirect oxidation (chlorine-mediated) were proved to be valid alternatives.